Physiological origin of biogenic magnetic nanoparticles in health and disease: from bacteria to humans - Gorobets O (Dove Medical Press, 2017)
Oksana Gorobets,1,2 Svitlana Gorobets,1 Marceli Koralewski3 1National Technical University of Ukraine (Igor Sikorsky Kyiv Polytechnic Institute), 2Institute of Magnetism, National Academy of Sciences, Kiev, Ukraine; 3Faculty of Physics, Adam Mickiewicz University, Poznan, Poland Abstract: The discovery of biogenic magnetic nanoparticles (BMNPs) in the human brain gives a strong impulse to study and understand their origin. Although knowledge of the subject is increasing continuously, much remains to be done for further development to help our society fight a number of pathologies related to BMNPs. This review provides an insight into the puzzle of the physiological origin of BMNPs in organisms of all three domains of life: prokaryotes, archaea, and eukaryotes, including humans. Predictions based on comparative genomic studies are presented along with experimental data obtained by physical methods. State-of-the-art understanding of the genetic control of biomineralization of BMNPs and their properties are discussed in detail. We present data on the differences in BMNP levels in health and disease (cancer, neurodegenerative disorders, and atherosclerosis), and discuss the existing hypotheses on the biological functions of BMNPs, with special attention paid to the role of the ferritin core and apoferritin. Keywords: biogenic magnetic nanoparticles, biomineralization, ferritin, magnetoferritin, genetic control, neurodegenerative disorders, cancer